Model in computer program to solve mass balance problems - Núñez Venegas, Oscar Julio (2012)
An important part of the development of process engineering is the calculation of the material balance, which is often very time consuming, especially when dealing with complex problems, because it involves analyzing a population of input variables and multiple simultaneous equations. This article presents a solution methodology through a computer program to facilitate calculations.